QTL and candidate genes associated with common bacterial blight resistance in the common bean cultivar Longyundou 5 from China - Jifeng Zhu; Jing Wu; Lanfen Wang; Matthew W. Blair; Zhendong Zhu; Shumin Wang (Crop Journal, 2016)
Common bacterial blight (CBB), caused by Xanthomonas axonopodis pv. phaseoli and Xanthomonas fuscans subsp. fuscans (Xff), is a worldwide disease of common bean (Phaseolus vulgaris L.). Longyundou 5, a Chinese cultivar in the Mesoamerican gene pool of common bean, displays resistance to the Xff strain XSC3-1. To identify the genetic mechanisms behind this resistance, we crossed Long 5 with a susceptible genotype to develop a mapping population of F2 plants. Plant resistance to CBB was identified at 14 and 21 days after inoculation with Xff strain XSC3-1. A major QTL at 14 and 21 days after inoculation was mapped on chromosome Pv10 with LOD scores of 6.41 and 5.35, respectively. This locus was associated with SAP6, a previously-identified and much-used dominant marker, but in a 4.2 cM interval between new codominant markers BMp10s174 and BMp10s244. Ten candidate genes were found between markers BMp10s174 and BMp10s244 on chromosome Pv10 and could encode defense response proteins responding to CBB pathogens. Four pairs each of epistatic QTL for CBB resistance were detected at 14 and 21 days after inoculation. Phenotypic variation explained by the epistatic QTL ranged from 7.19% to 12.15% and 7.72% to 8.80% at 14 and 21 days after inoculation, respectively. These results confirmed the importance of epistasis in CBB resistance in common bean. The adjacent markers found may be more efficient for marker assisted selection in common bean breeding for CBB resistance owing to their closer linkage to the target QTL.